The civilizational role of Islam in the Indian subcontinent: the Delhi Sultanate - Islam, Arshad (Yeni Turkiye Staratejik Arastirma Merkezi, 2017)
Muslim presence was manifest in the co astal regions o f Southern India from the earliest days o f Islam, as evidenced by the establishment o f Arab trading settlements, with m inor political impact prior to the conquests in Northern India from the beginning o f the 8th century, w hich solidified the influence o f Islam leading to tangible political and socio-cultural impacts in the region. The history o f India furnishes an amazing picture o f the syntheses o f many divergent cultural trends w hich w ere gradually transformed by a process o f mutual adjustment and assimilation. Islam played a significant role in this by contributing to India’s multi-cultural and multi-religious ethos, em bedding the subcontinent in the Arab-Islamic maritim e civilization, stretching from southern Africa to China, particularly in connecting Africa as w ell as the great Turkic em pires o f Central Asia. It offers a pertinent example o f the interaction o f human minds and the effects o f cultural and civilizational contacts on indigenous customs, religion, literature and arts. This paper examines the impact o f Islam in the Indian Peninsula from three different angles: its political predominance, its intellectual and cultural impact, and finally, its influence on art and architecture. Based mainly on Arabic and Persian sources, the article focu ses on the intellectual legacy, achievem ents and the role that the Indian